Bound lengths based on constant-stress PALT under different censoring patterns - Prakash, Gyan; Singh, Prabhakar (International Journal of Scientific World, 2017)
The Gompertz distribution is assumed in the present article for drawing the inferences based on Bayesian methodology. Constant-Stress Partially Accelerated Life Test (CS-PALT) have used for the underlying distribution on first-failure Progressive (FFP) censoring scheme. All special cases of the FFP censoring scheme have used for the present comparative analysis. The comparison has been done between different special cases of FFP based on Approximate Confidence Lengths (ACL) under Normal approximation, Bootstrap Confidence Length (BCL) and One-Sample Bayes Prediction Bound Lengths (BPBL). A simulation study have been carried out for the present analysis. Â